2012
DOI: 10.1111/j.1365-2621.2012.03081.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of wheat flour and quality characteristics of pan bread as modified by partial additions of wheat bran or whole grain wheat flour

Abstract: The use of bran and whole grain flour changes dough rheology and causes difficulties in manufacturing bakery products. The aim of this study was to analyse the influence of substituting refined wheat flour (WF) by wheat bran (WB; 5%, 10%, 20%, 30% and 40%) or whole grain wheat flour (WGWF; 10%, 20%, 30%, 40% and 50%) on dough rheological properties and pan bread quality characteristics. The addition of WB and WGWF increased water absorption and resistance to extension and decreased stability, extensibility and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
70
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 18 publications
12
70
1
1
Order By: Relevance
“…The collected data confirm the effects on the rheological properties of dough when refined The control (no replacement) and the 5%-, 10%-, 15%-, 20%-, 25%-substituted breads 6 were produced using the previously described flours and were first analyzed for their 7 technology properties: crust color, bread crunchiness and volume, TPA test. (Table 2).…”
supporting
confidence: 65%
See 2 more Smart Citations
“…The collected data confirm the effects on the rheological properties of dough when refined The control (no replacement) and the 5%-, 10%-, 15%-, 20%-, 25%-substituted breads 6 were produced using the previously described flours and were first analyzed for their 7 technology properties: crust color, bread crunchiness and volume, TPA test. (Table 2).…”
supporting
confidence: 65%
“…An increase in substitution with the pearled fraction resulted in a The results of the mechanical and acoustical properties of the composite bread crust are 5 reported in Table 2. The total break energy, that is the energy necessary to break the crust 6 and to continue the compression until 20 mm of penetration, was found to be higher in the 7 0% and 5% flour substituted samples, with a descending trend when the flour replacement 8 level was increased (from 149 mJ to 99 mJ, -35.6%).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Protein was highly correlated with hardness of bread (r = 0.912) in Korean wheat indicating a difference in protein quality between the imported wheat and Korean wheat samples used in this study. Lin et al (2012) and Schmiele et al (2012) reported a high correlation between SV of bread and dough extensibility. In addition, Lin et al (2012) showed that bread made with flour containing high gluten content exhibited the highest SV.…”
Section: Relationship Between Flour Dough and Bread Parametersmentioning
confidence: 92%
“…In the present study, the increase in WA of WM compared with WF was most probably related with the higher bran content consequently the higher total pentosan content of WM. Schmiele et al (2012) pointed out that the addition of whole wheat flour or wheat bran to WF causes an increase in the bran content of flour blend leading to an increase in WA (Bucsella et al 2016).…”
Section: Farinographic Properties Of Wheat Meal and Flourmentioning
confidence: 99%